Evidence and Interpretation in Studies on Early Science and Medicine : Essays in Honor of John E. Murdoch - Murdoch, John Emery, 1927-2010; Sylla, Edith Dudley; Newman, William R., 1955- (Brill, 2009)
Containing sixteen essays and a substantial introduction by noted historians of premodern science, this book provides a fresh look at divergent yet complementary traditions of interpreting the natural world, ranging from Greek mechanics to early modern Chinese theories of dragons.